Characterization and identification of nitrogenfixing bacteria isolated from agricultural soil - Tran Thi Thuy Ha; Thai Thi Lam; Nguyen Thanh Huyen; Nguyen Xuan Canh (Vietnam Journal of Science, Technology and Engineering, 2018)
To isolate and characterise free nitrogen-fixing bacteria, we collected randomly soil samples from different areas of Ha Noi. Nitrogen-fixing bacteria were isolated using Burk’s medium without nitrogen mineral supplement. The ammonia (NH4+) synthesis of these bacterial strains after biomass production was determined by means of Nessler reagent. Based on the results of isolation, we observed and evaluated colony and cellular morphology, pigment production, and metabolic activities of twenty-five isolates. Among the isolated bacteria, two bacterial strains (6.2 and 8.2) with high NH4+ concentration in the cultural medium were selected as the best strains for nitrogenfixing ability. The optimal pH and temperature for their growth and nitrogen fixation are 7.0 and 30°C, respectively. Growth is best favored in the presence of sucrose. We sequenced the 16S rRNA gene of selected strains and compared the homology of them in GenBank using BLAST search. The result of the comparison shows that the 6.2 and 8.2 strains have 99% and 100% 16S rRNA-sequence similarity with Pseudomonas sp. and Bacillus sp., respectively.